Power play - Pearson, Ridley (Kingdom keepers, 2012)
When a group of Disney villains known as the Overtakers threaten to release two of their leaders from Disney captivity, the five teens of the Kingdom Keepers must work together to protect the Disney magic and keep the evil locked up.